Emergency management for preventing and controlling nosocomial infection of the 2019 novel coronavirus: implications for the dermatology department. (20th April 2020) - Tao, J.; Song, Z.; Yang, L.; Huang, C.; Feng, A.; Man, X.
Abstract : Plain language summary available online